Unleashing the Power of Visuals: A Captivating Exploration of Scientific Data Visualization Methods and Techniques - Baharum A.; Ismail R.; Ismail I.; Mat Noor N.A.; Deris F.D.; Halamy S. (Springer Science and Business Media Deutschland GmbH, 2025)
Scientific visualizations are the building blocks for conveying results and ideas to a wide range of audiences. It is one of the steps in the data science process, and it should be done before the data presentation phase. Because some data is not easy to read for humans, visualization can help transform the data into visual content such as graphs or plots, as the requirement for scientific visualization techniques and methods is increasing greatly. Reviewing various visualization methods is necessary to increase knowledge about it. In this paper, an overview of scientific data visualization methods and techniques has been reviewed. To conduct the experiment, a total of five peer-reviewed articles relating to scientific visualization techniques were chosen. The problem with this study is that people still do not have a clear idea of how to use or what is the importance of scientific visualization. The findings of this paper show that the occurrence of visualization techniques improves the effectiveness of reading data and helps people to understand data in a more vivid way. A systematic literature review has been adopted in this study to assist the author in doing a study without bias. Finally, this paper can help readers increase their knowledge of the scientific visualization technique. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.